Improving the Quality of Host Country Ethical Oversight of International Research: The Use of a Collaborative ‘Pre-Review’ Mechanism for a Study of Fexinidazole for Human African Trypanosomiasis - Coleman, Carl H.; Ardiot, Chantal; Colonna, Pierre; Ecuru, Julius; Edielu, Andrew; Strub-Wourgaft, Nathalie (Developing World Bioethics, 2015)
Developing countries face numerous barriers to conducting effective and efficient ethics reviews of international collaborative research. In addition to potentially overlooking important scientific and ethical considerations, inadequate or insufficiently trained ethics committees may insist on unwarranted changes to protocols that can impair a study's scientific or ethical validity. Moreover, poorly functioning review systems can impose substantial delays on the commencement of research, which needlessly undermine the development of new interventions for urgent medical needs. In response to these concerns, the Drugs for Neglected Diseases Initiative (DNDi), an independent nonprofit organization founded by a coalition of public sector and international organizations, developed a mechanism to facilitate more effective and efficient host country ethics review for a study of the use of fexinidazole for the treatment of late stage African Trypanosomiasis (HAT). The project involved the implementation of a novel ‘pre-review’ process of ethical oversight, conducted by an ad hoc committee of ethics committee representatives from African and European countries, in collaboration with internationally recognized scientific experts. This article examines the process and outcomes of this collaborative process.
Keywords: clinical trials; research ethics; international justice; committees; research; informed consent